The Message is Murder Substrates of Computational Capital - Beller, Jonathan (Pluto Press, 2017)
The Message is Murder analyses the violence bound up in the everyday functions of digital media. At its core is the concept of 'computational capital' - the idea that capitalism itself is a computer, turning qualities into quantities, and that the rise of digital culture and technologies under capitalism should be seen as an extension of capitalism's bloody logic.Engaging with Borges, Turing, Claude Shannon, Hitchcock and Marx, this book tracks computational capital to reveal the lineages of capitalised power as it has restructured representation, consciousness and survival in the twentieth and twenty-first centuries.Ultimately The Message is Murder makes the case for recognising media communications across all platforms - books, films, videos, photographs and even language itself - as technologies of political economy, entangled with the social contexts of a capitalism that is inherently racial, gendered and genocidal.